Studies on the Consumption, Digestion and Utilisation of Food Plants by Pericallia ricini - Ranjith A M (Department of Agricultural Entomology, College of Horticulture, 1981)
The present investigation was carried out in the Entomology Department of the College of Horticulture, Vellanikkara. It was aimed at working out idices relating to consumption, digestion and utilisation of eight food plants by the larvae of Pericallia ricini F., a polyphagous pest in Kerala. The study was also meant to assess the relative growth of the caterpillars on the different food plants so that a general idea can be obtained on the suitability of the food plants to the larvae. Data on the pupal and adult emergence were also collected with a view to probing further in to the identification of probable insect growth inhibitory substances among the host plants. The most preferred plants with regard to the consumption of foliage were pumpkin, castor and brinjal. Consumption index was calculated on fresh and dry weight bases. It was seen that the consumption of brinjal leaves was the maximum and the index was the least for sweet potato. The other foods did not differ among them significantly. On dry weight basis, banana-fed insects with a C.I. of 3.02 ranked first, followed by larvae fed on cotton. Larval weight gain on brinjal was the maximum followed by those grown on pumpkin. The least weight gain of 0.66 g was exhibited by larvae which were fed on banana leaves. The last instar larvae consumed the largest quantity of food during their larval period. Consumption of food was very low among the third instar larvae. Females were to consume more foliage than the corresponding male counterparts. The differences in consumption by the two sexes were statistically significant. The growth rates were calculated both on fresh and dry weight basis. On fresh weight basis, larvae reared on brinjal had the highest growth rate of 65.7 and the least growth rate of 30.7 was obtained from larvae grown on banana. On dry weight basis, it was seen that pumpkin was superior to all others in supporting larval growth of P. ricini. The approximate digestibility was calculated on the basis of fresh weight of the digestible food and the weight of the ingested food. A.D. was the maximum (91.40 per cent) with sesamum on fresh weight basis, but on dry weight basis, it was castor that the larvae digested most. Indices relating to efficiencies of converting ingested food and digested food to biomass were also calculated both on fresh and dry weight bases. The reasons for the observed values deviating from the expected ones are discussed. Utilisation of nitrogen, both ingested and digested, by the larvae varied among food plants significantly. Colocasia, sesamum and cotton had the higher values of E.C.I. (N). In the descending order. But taking into consideration of the E.C.D. (N) values, the numerical figure was the highest with castor and the least with banana. The present study has clearly indicated that the food plants have a significant effect on the pupal period, pupal weight and pupal length. It is also seen that some host plants cause larval and pupal mortalities at varying degrees. The effect of larval feeding on the sex ratio of emerging adults was also recorded. Insects fed on castor and cotton leaves showed the near best sex ratio of 1: 0.88. In the case of sweet potato and sesamum, the ratio was 1: 2. All other foods led to sex ratios ranging from 1:0.67 to 1: 2.